A new bivariate beta distribution of Kind-1 of Type-A. Issue 1 (2nd January 2019) - David Sam Jayakumar, G. S.; Sulthan, A.; Samuel, W.
Abstract: This paper proposes a new form of bivariate beta distribution of Kind-1 of Type-A as well as the density function is visualized in terms of Generalised hypergeometric function and the marginals are univariate beta distribution of Kind-1. Moreover, conditional distributions and constants of the conditionals are also computed. Generating functions such as moment, Cumulant, characteristic functions and the Shannon's differential entropy are also determined. The Bivariate correlations between the random variables for different combination of shape parameters are tabulated and three dimensional probability surfaces are used to visualize the shape of the derived densities graphically. Finally, the special cases of the distribution such as Bivariate Beta distribution of Kind-2 of Type-A, Bivariate F-distribution of Kind-1, Bivariate uniform distribution, Different forms of Bivariate Kumaraswamy distribution, Bivariate exponential and exponentiated distribution, Bivariate Wigner distribution and Bivariate Arcsine distribution are also discussed.